Efektivitas Model Pembelajaran Generatif: Pemahaman dan Keterlibatan Siswa dalam Pembelajaran Matematika - Saddam Hussein; Khoiruzzadittaqwa, Muhammad (AB-JME: Al-Bahjah Journal of Mathematics Education, 2024)
Enhancing the quality of mathematics education requires innovative and interactive teaching approaches. Generative Learning Model offers a framework that allows students to actively participate in the learning process, potentially improving their understanding of mathematical concepts. This research aims to conduct a systematic analysis of existing literature on the use of Generative Learning Model in mathematics education, focusing on effective strategies for developing interactive and effective learning tools. The research methodology involves developing a review protocol, conducting a comprehensive literature search through databases such as Google Scholar, and selecting studies using the PRISMA flowchart. The results of the analysis show that the Generative Learning Model can significantly improve mathematical concept understanding and student engagement. Effective strategies in developing learning tools based on the Generative Learning Model include the use of interactive tools and contextual approaches in teaching. The conclusions of this research confirm that the use of the Generative Learning Model contributes positively to the interactivity and effectiveness of mathematics learning, and provides recommendations for further research and practical application in educational contexts.